2018
DOI: 10.1002/jcp.27340
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NEAT1 represses inflammation response and lipid uptake via modulating miR‐342‐3p in human macrophages THP‐1 cells

Abstract: Atherosclerosis has been recognized as a chronic inflammation process induced by lipid of the vessel wall. Oxidized low-density lipoprotein (ox-LDL) can drive atherosclerosis progression involving macrophages. Recently, long noncoding RNAs (lncRNAs) have been reported to play critical roles in atherosclerosis development. In our current study, we focused on the biological roles of lncRNA NEAT1 in atherosclerosis progress. Here, we found that ox-LDL was able to trigger human macrophages THP-1 cells, a human mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 32 publications
6
76
0
2
Order By: Relevance
“…LncRNAs are pivotal regulators of gene functions and various cellular processes (Wang et al, 2018Yamazaki et al, 2018). The lncRNAs have been found to be involved in subcellular architecture, protein complex stabilization, as well as in physiology and pathophysiology (Del Vecchio et al, 2018;Gutschner et al, 2018;Liu et al, 2018;Wang et al, 2019;Yan et al, 2019;Yu et al, 2019). Within the last few years, numerous studies have shown that nuclear enriched abundant transcript 1 (NEAT1) play crucial roles both in carcinogenesis and non-cancerous diseases such as neurodegeneration and inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are pivotal regulators of gene functions and various cellular processes (Wang et al, 2018Yamazaki et al, 2018). The lncRNAs have been found to be involved in subcellular architecture, protein complex stabilization, as well as in physiology and pathophysiology (Del Vecchio et al, 2018;Gutschner et al, 2018;Liu et al, 2018;Wang et al, 2019;Yan et al, 2019;Yu et al, 2019). Within the last few years, numerous studies have shown that nuclear enriched abundant transcript 1 (NEAT1) play crucial roles both in carcinogenesis and non-cancerous diseases such as neurodegeneration and inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study shows that lncRNA NEAT1 is overexpressed in myocardial IR injury mice models and lncRNA NEAT1 knockdown represses levels of pro‐inflammatory cytokines (TNF‐α, IL‐1β, and IL‐6), decreases troponin level, reduces cardiocytes apoptosis, and inhibits release of lactate LDH in vitro . Besides, a study displays that lncRNA NEAT1 knockdown inhibits levels of IL‐6, IL‐1β, cyclooxygenase‐2 (COX‐2), and TNF‐α via regulating miR‐342‐3p in human macrophages THP‐1 cells . For stroke, a study discloses that lncRNA NEAT1 upregulation enhances OGD/R injury‐induced inflammatory response in cerebral microglial cells through Wnt/β‐catenin signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NEAT1, as an abundant and ubiquitously expressed lncRNA, has been reported to be a pivotal factor in the pathology of various diseases, including cardiovascular and cerebrovascular diseases. [14][15][16] For example, a study shows that lncRNA NEAT1 is overexpressed in myocardial IR injury mice models and lncRNA NEAT1 knockdown represses levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), decreases troponin level, reduces cardiocytes apoptosis, and inhibits release of lactate LDH in vitro. 14 Besides, a study displays that lncRNA NEAT1 knockdown inhibits levels of IL-6, IL-1β, cyclooxygenase-2 (COX-2), and TNF-α via regulating miR-342-3p in human macrophages THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations